Aplicación web para la gestión y envío de notificaciones mediante SMS a los Padres de Familia del Centro de Educación Básica Particular “Neptalí Pacheco León” - Frutoso Cajas, Marjorie Alexandra (2019)
As information and communication technologies are constantly advancing, in order to offer a better quality of services, most institutions seek to adapt to these changes so as not to get stuck in a technological gap, which small businesses suffer. However, educational institutions also seek to improve the processes that are carried out manually, which is why they use technology to automate them, reducing time and helping the information to be handled in an integral and reliable manner. Taking into account that education is the main axis for the growth of a country, in addition to teaching to write and read, teachers inculcate values ​​and principles which are important for the development of children, it is convenient to remember that this responsibility should be shared between Teachers and Parents. As in this proposal of information, communication and technological undertakings, the development of a web application for the management and sending of notifications by SMS will be carried out, perfectly fits the line of research, Software Engineering and Programming.